2017
DOI: 10.1109/tla.2017.8070421
|View full text |Cite
|
Sign up to set email alerts
|

A Fault-Tolerant Algorithm For Distributed Resource Allocation

Abstract: Abstract-Resource allocation is a usual problem that must be faced during a distributed system design. Despite the large number of algorithms proposed in literature to solve this problem, most papers lack of detailed descriptions about how to turn these algorithms into real-world reliable protocols. This article presents a fault-tolerant algorithm for distributed resource allocation named SLOTS which is implemented as an executable protocol. It allocates resources among members in a fairly manner using simple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…After visualization, it can be observed that the geometric properties of the corresponding two sets of words in the two languages are similar to each other [13].…”
Section: Bilinear Methods Based On Distributed Computingmentioning
confidence: 92%
“…After visualization, it can be observed that the geometric properties of the corresponding two sets of words in the two languages are similar to each other [13].…”
Section: Bilinear Methods Based On Distributed Computingmentioning
confidence: 92%
“…To sum up, it is very feasible to find, design and implement a multilayer distributed structure teaching management system. In this regard, this paper conducts a comprehensive evaluation on the informatization of distributed teaching management [18].…”
Section: Operational Feasibilitymentioning
confidence: 99%